Artificial Neural Network (ANN) - Meta EP technique for lighting prediction / Zuhaida Hanapi - Hanapi, Zuhaida (2009)
Malaysia has high lightning and thunderstorm occurrences throughout the year because it is situated near the equator line which is characterized by high lightning and thunderstorm activity. With the existing and availability of many sophisticated instrument, weather data can be recorded easily. By using these data, some efforts are being made in order to improve the prediction of weather conditions with great potentiality. This project presents the development of Meta-Evolutionary Programming (EP) and Artificial Neural Network (ANN) prediction system for lightning occurrence based on historical lightning and meteorological data.